PENGELOLAAN BELANJA DAERAH: APAKAH SISTEM AKUNTANSI KEUANGAN DAERAH, PENGAWASAN KEUANGAN DAERAH, DAN KOMPETENSI SUMBER DAYA MANUSIA BERPENGARUH? - Yuliana, Eva; Aliamin, Aliamin (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2023)
This study aims to analyze the effect of regional financial accounting systems, regional financial supervision, and human resource competence on regional expenditure management. This study is descriptive quantitative research. The population in this study is the SKPD of Aceh Tengah District. The sampling method used was random sampling with a total of 220 respondents. The type of data used is primary data obtained through distributing questionnaires. The data were analyzed using multiple linear regression analysis with the help of IBM SPSS Statistics 25. The finding indicated that the regional financial accounting system has a positive and significant effect on regional expenditure management, regional financial supervision has a positive and significant effect on regional expenditure management, and human resource competence has a positive and significant effect on regional expenditure management. Simultaneously, regional financial accounting systems, regional financial supervision, and human resource competence have a positive and significant effect on regional expenditure management.